Influences of school climate on emotional health and academic achievement of school-going adolescents in India: a systematic review - Jayalaxmi Kaniyagundi Podiya; Janardhana Navaneetham; Poornima Bhola (BMC Public Health)
Abstract Background As students spend most of their time in school, a supportive school environment is essential for adolescents’ personal growth, effective learning, and well-being. Students actively participate in learning when they feel supported, respected, and connected to their school environment. An unhealthy school climate might significantly influence health-related and educational outcomes during adolescence. Therefore, a positive and supportive school climate can contribute significantly to the emotional health as well as academic achievement of adolescents. Methods The present systematic review explores the relationships among school climate, emotional health outcomes, and academic achievements among school-going adolescents in India. The study was registered with PROSPERO (CRD42024567954). A systematic literature search was conducted across multiple databases, such as PsycINFO, EBSCO Host (Psychology and behavioral sciences collection), PubMed, ERIC, Web of Science, ProQuest Dissertations & Theses Global: The Humanities and Social Sciences Collection, Shodhganga, Cochrane Library, and Google Scholar which are recognized sources of high-quality publications. It covered published as well as unpublished research studies, including peer-reviewed journals and gray literature, such as reports of programs on the impact of the school climate on the emotional health and academic achievement of adolescents between January 2000 and December 2023. An initial search returned a total of 383 studies screened by two reviewers. After the title and abstract screening, 30 studies were left out for full-text review, and ultimately, eleven studies have remained for the present systematic review. Results The findings of the current review indicated that positive school climate characteristics such as student-teacher relationships, peer support, a sense of connectedness, school belongingness, methods of learning, and teaching were significantly associated with reduced symptoms of depression, stress, improved self-esteem, and academic performance among high school students. These results demonstrated the important role of a protective and supportive school climate in promoting overall well-being and educational achievements among Indian adolescents. Conclusions The review considerably evidenced the significance of school climate in determining school-going adolescents’ emotional health and academic achievement. This indicated the requirement to implement school-based intervention packages in secondary schools to improve the school climate. The whole school approach could be a better strategy for intervention. Clinical trial number Not applicable.